Wolf pack : a Joe Pickett novel - Box, C. J (Box, C. J. Joe Pickett novel, 2019)
Wyoming game warden Joe Pickett encounters bad behavior on his own turf--only to have the FBI and the DOJ ask him to stand down--in the thrilling new novel from #1 New York Times-bestselling author C.J. Box.